TAECHER EDUCATION INSTITUTE OF MALAYSIA (IPGM) LECTURERS ASPIRATIONS IN ENHANCING CAPABILITIES IN THE DIGITAL INNOVATION FIELD - Hairul Faiezi Bin Lokman; Shamsazila Binti Sa'aban; Siti Rosni Binti Mohamad Yusoff; Aliza Binti Adnan; Azerai Bin Azmi (Journal Civics And Social Studies, 2022)
Digital innovation in the education sector is a necessity today to face the challenges of the Industrial Revolution 5.0 era. With the threat of the Covid-19 pandemic, digital innovation is also seen as a driver of learning to reform new norms that make information technology a medium for empowering educational institutions throughout the world. The Teacher Education Institute of Malaysia (IPGM) is also optimistic about fostering digital innovation among lecturers to form an education enabler circle that is able to apply digital innovation for exposure to prospective teachers (students). Therefore, this survey study was conducted to identify the aspirations of IPGM lecturers to improve their abilities in implementing digital innovation. Subjective items for the open-ended questions were prepared using Google Forms. The findings of this research show that several aspirations of IPG lecturers in improving their abilities in the field of digital innovation include aspirations for innovation, training, funding assistance, infrastructure assistance and commercialization assistance.